NEPA as antiemetic prophylaxis after failure of 5HT3-RA plus dexamethasone in patients receiving carboplatin and gemcitabine chemotherapy: A monocentric real-life experience. (April 2021) - Valerio, Maria Rosaria; Gebbia, Vittorio; Borsellino, Nicolò; Vecchia, Maria La; Serretta, Vincenzo; Pardo, Salvatore; Cipolla, Calogero; Galanti, Daniele
Introduction: Chemotherapy-induced nausea and vomiting (CINV) may affect adherence to planned chemotherapy treatments and compromise patients' quality of life during the therapy. NEPA is an oral fixed combination of netupitant, a highly-selective NK1 -RA and palonosetron, a 5HT3 -RA, approved for the prevention of acute and delayed CINV. The aim of this study was to evaluate the efficacy and safety of NEPA with dexamethasone for CINV prophylaxis in the challenging setting of carboplatin and gemcitabine combination chemotherapy, after failure of prophylaxis with 5HT3 receptor antagonist. Methods: Eligible patients were undergoing carboplatin and gemcitabine combination chemotherapy for metastatic non-small cell lung cancer (NSCLC), ovarian cancer or urothelial cancer and experienced nausea and/or vomiting after the first cycle of chemotherapy, despite an antiemetic prophylaxis with a 5HT3 -RA and dexamethasone. Primary efficacy endpoint was complete response (CR: no emesis, no rescue medication) obtained with NEPA, during the overall phase (0–120 h), after the start of chemotherapy. Results: During the first cycle of chemotherapy, 15 out of 30 (50%) patients did not properly control CINV with a 5HT3 -RA plus dexamethasone used as primary antiemetic prophylaxis and then were switched to NEPA from the subsequent cycle. During NEPA administration, 13 out of 15 patients (86.7%) achieved an overall CR (no emesis, no rescue medication). Antiemetic treatment with NEPA was very well tolerated with only two patients (13.3%) that experienced a grade 1 TEAE. Conclusions: Our experience showed that NEPA has proven to be very effective and well tolerated in the prophylaxis of CINV induced by carboplatin-based chemotherapy.